Hormonal contraceptives impair psychomotor vigilance task performance under sleep deprivation with stress induction. - Kennedy, Kathryn E R; Huskey, Alisa; Negelspach, David C; Cha, Jungwon; Patel, Salma I; Satterfield, Brieann C; Killgore, William D S (Sleep Advances, 2026)
Study Objectives Hormonal contraceptives (HC) have been shown to influence cognitive performance, yet their effects under conditions of sleep deprivation remain poorly understood. Consistent with prior research demonstrating greater fatigue among individuals using HC, we hypothesized that vigilant attention would be impaired among females using HC compared with males and females not using HC. Methods Forty-eight participants (18–30 years; 23 females) underwent 28 hours of total sleep deprivation (TSD) while completing serial stress tasks, psychomotor vigilance tasks (PVT), and providing salivary cortisol samples. Mixed-effects models were constructed with either PVT outcomes or cortisol reactivity as dependent variables, group (males, females not using HC, females using HC) time, and mood induction group as fixed effects, as well as a group-by-time interaction, and participant as a random effect. Results Females using HC demonstrated significantly more PVT lapses (F(1,45) = 3.75; p  = .031) and a trend toward lower PVT speed (F(2,44) = 3.05; p  = .057) than males and females not using HC during the second half of the sleep deprivation period. No significant group differences were observed for PVT reaction time or false starts. Neither self-reported sleepiness, cortisol reactivity, or amplitude differed by group. Conclusions Use of HC was associated with greater attentional instability following TSD, reflected by increased lapses and reduced vigilance efficiency. These effects occurred independently of cortisol responses. Larger studies are needed to further characterize the cognitive effects of HC use under sleep loss and to elucidate underlying mechanisms. Statement of Significance Steroid sex hormones, such as estrogen and progesterone, exhibit 24-hour rhythms and fluctuate throughout the menstrual cycle in females of reproductive age. These rhythms are altered among individuals using hormonal contraceptives and relatively little is understood about how this influences cognition. Even less is understood about how these medications influence sleep or cognitive performance under sleep deprivation. In this study, individuals using hormonal contraceptives demonstrated significantly poorer performance on a psychomotor vigilance task than males or females not using hormonal contraceptives during the latter half of a 28-hour total sleep deprivation period. These findings highlight the need for further investigation into the effects of hormonal contraceptives on cognitive functioning, particularly under conditions of sleep loss.